The effect of stellar contamination on low-resolution transmission spectroscopy: needs identified by NASA's Exoplanet Exploration Program Study Analysis Group 21. Issue 1 (22nd March 2023) - Rackham, Benjamin V; Espinoza, Néstor; Berdyugina, Svetlana V; Korhonen, Heidi; MacDonald, Ryan J; Montet, Benjamin T; Morris, Brett M; Oshagh, Mahmoudreza; Shapiro, Alexander I; Unruh, Yvonne C; Quintana, Elisa V; Zellem, Robert T; et al.
Abstract: Study Analysis Group 21 (SAG21) of NASA's Exoplanet Exploration Program Analysis Group was organized to study the effect of stellar contamination on space-based transmission spectroscopy, a method for studying exoplanetary atmospheres by measuring the wavelength-dependent radius of a planet as it transits its star. Transmission spectroscopy relies on a precise understanding of the spectrum of the star being occulted. However, stars are not homogeneous, constant light sources but have temporally evolving photospheres and chromospheres with inhomogeneities like spots, faculae, plages, granules, and flares. This SAG brought together an interdisciplinary team of more than 100 scientists, with observers and theorists from the heliophysics, stellar astrophysics, planetary science, and exoplanetary atmosphere research communities, to study the current research needs that can be addressed in this context to make the most of transit studies from current NASA facilities like Hubble Space Telescope and JWST . The analysis produced 14 findings, which fall into three science themes encompassing (i) how the Sun is used as our best laboratory to calibrate our understanding of stellar heterogeneities ('The Sun as the Stellar Benchmark'), (ii) how stars other than the Sun extend our knowledge of heterogeneities ('Surface Heterogeneities of Other Stars'), and (iii) how to incorporate information gathered for the Sun and other stars into transit studies ('Mapping Stellar Knowledge to Transit Studies'). In this invited review, we largely reproduce the final report of SAG21 as a contribution to the peer-reviewed literature.